2004
DOI: 10.1542/peds.114.2.e264
|View full text |Cite
|
Sign up to set email alerts
|

Pertussis Pneumonia, Hypoxemia, Hyperleukocytosis, and Pulmonary Hypertension: Improvement in Oxygenation After a Double Volume Exchange Transfusion

Abstract: ABSTRACT. A 3-month-old infant of 33 weeks' gestation was hospitalized with pneumonia caused by Bordetella pertussis. Respiratory insufficiency worsened, and on hospital day 3, there was severe pulmonary dysfunction (arterial oxygen pressure/fraction of inspired oxygen ratio: 120), extreme leukocytosis (white blood cell count 104 000/mm 3 ), and severe pulmonary hypertension as assessed by 2-dimensional echocardiogram. A double volume exchange transfusion was performed to reduce the leukocyte mass. Oxygenation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
0
16

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(63 citation statements)
references
References 12 publications
1
46
0
16
Order By: Relevance
“…Emergent leukapheresis or exchange transfusion has been advocated for hyperleukocytosis accompanied by respiratory distress or cardiovascular instability. [13][14][15] Exchange transfusion is not recommended for the neonate with asymptomatic leukemoid reaction. A recent review of 1200 infants with birth weight <2500 g revealed 17 cases of leukemoid reaction with peak WBC count at 9 days of age.…”
Section: Discussionmentioning
confidence: 99%
“…Emergent leukapheresis or exchange transfusion has been advocated for hyperleukocytosis accompanied by respiratory distress or cardiovascular instability. [13][14][15] Exchange transfusion is not recommended for the neonate with asymptomatic leukemoid reaction. A recent review of 1200 infants with birth weight <2500 g revealed 17 cases of leukemoid reaction with peak WBC count at 9 days of age.…”
Section: Discussionmentioning
confidence: 99%
“…La reposición se efectúa con glóbulos rojos desplamatizados, o bien con una combinación de una solución de albúmina al 4,5% y un concentrado de glóbulos rojos para alcanzar un nivel final de hematocrito de 0,40 a 0,45. 23 La citorreducción como tratamiento de la coqueluche grave se inicia en 2004, 9 y existe actualmente un algoritmo terapéutico propuesto por Rowlands y cols., 23 (Figura 2), quienes reportan, en su trabajo, una disminución en la mortalidad esperada con dicho tratamiento.…”
Section: Manejo Terapéutico En Las Unidades De Cuidados Intensivosunclassified
“…9 Reportan sobre dicho procedimiento en una paciente de 3 meses de edad con coqueluche grave, HTP observada por ecocardiograma y con ARM, con resultado satisfactorio en la reducción de la masa leucocitaria, con un valor preexanguinotransfusión de GB de 104 000 mm 3 y un recuento posterior al procedimiento de 15 200 mm 3 . Constatan una mejoría en los parámetros de oxigenación (PaO 2 /FiO 2 ) y en los signos indirectos de HTP.…”
Section: Tratamientos De Leucorreducciónunclassified
“…La TP es un conocido factor promotor de leucocitosis periférica, y en forma indirecta refleja también la cantidad de bacterias implicadas 75,79,86 . Esto generaría el desarrollo de trombos microvasculares lo que asociado a un sistema de coagulación y fibrinolítico inmaduro, generaría un síndrome de hiperviscosidad sanguínea y trombosis de las arteriolas pulmonares 80, 81,87 . Sin embargo, otros autores postulan que tras la HTP existiría un proceso vasculítico local, más que un vasoespasmo, secundario al daño del epitelio respiratorio y progresivamente del endotelio vascular, mediado por citoquinas liberadas desde los linfocitos 27,28 .…”
Section: Fisiopatologíaunclassified